2021
DOI: 10.1021/acsomega.1c03694
|View full text |Cite
|
Sign up to set email alerts
|

WO3/Ag2CO3 Mixed Photocatalyst with Enhanced Photocatalytic Activity for Organic Dye Degradation

Abstract: The development of an efficient photocatalyst with superior activity under visible light has been regarded as a significant strategy for pollutant degradation and environmental remediation. Herein, a series of WO 3 /Ag 2 CO 3 mixed photocatalysts with different proportions were prepared by a simple mixing method and characterized by XRD, SEM, TEM, XPS, and DRS techniques. The photocatalytic performance of the WO 3 / Ag 2 CO 3 mixed photocatalyst was investigated by the degradation of rhodamine B (RhB) under vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The main oxidative and reactive species were electrons and cOH radicals, holes were the minor oxidative species, and O 2 c − has considerable effects on the degradation of diclofenac. The cOH radicals can be obtained in two ways, as shown in eqn ( 11)- (13). In eqn (11), molecular O 2 reacts with the electrons (e − ) in the CB and resulted in O 2 c − .…”
Section: Metal Oxides In Photocatalytic Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…The main oxidative and reactive species were electrons and cOH radicals, holes were the minor oxidative species, and O 2 c − has considerable effects on the degradation of diclofenac. The cOH radicals can be obtained in two ways, as shown in eqn ( 11)- (13). In eqn (11), molecular O 2 reacts with the electrons (e − ) in the CB and resulted in O 2 c − .…”
Section: Metal Oxides In Photocatalytic Degradationmentioning
confidence: 99%
“…Then, O 2 c − reacts with water molecules to produce cOH radical species, as shown in eqn (12). On the other hand, as shown in eqn (13), the h + can react with H 2 O on the surface of photocatalyst to produce cOH radical species.…”
Section: Metal Oxides In Photocatalytic Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver-based semiconductor materials have received significant attention for photocatalysis applications owing to their excellent bandgap and structural stability [11][12][13]. For instance, AgX-based (Cl, Br, and I) [14][15][16][17][18][19][20] semiconductors exhibit notable visible-sunlight harvesting and could be used to remove organic contaminants from water systems. Silver tungstate (Ag 2 WO 4 ) has also been extensively explored as a semiconductor photocatalyst for the decontamination of organic pollutants [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various studies have been conducted to enhance photocatalytic activity of the WO3 photocatalysts. Many previous studies have been reported that combination of WO3 with another photocatalyst to establish a heterojunction system could enhance electron and hole separation efficiency as well as prevent the recombination of photo-excited electrons and holes leading to increase in its photocatalytic activity [4,9,10]. Due to its high stability and responsiveness to visible light, silver vanadate (Ag3VO4), another moderate band gap energy material that has attracted significant attention [11][12][13].…”
Section: Introductionmentioning
confidence: 99%